RELATIVE EFFICACY OF THE CAPITAL MARKET OVER THE MONEY MARKET IN A GROWTH-FINANCING ECONOMY - Adedeji Daniel Gbadebo (Gusau Journal of Accounting and Finance)
This study investigates if the Nigerian capital market is more effective in impacting economic growth compared with the money market. The paper uses a growth model that depend on usual labour and capital, as well as incorporates the money and capital market variables to produce outputs. The study uses data from the Central Bank of Nigerian and Securities and Exchange Commission Bulletins between from 1981 and 2020. The paper finds the existence of a long-run link amidst the money market, capital market and growth. In the short- and long run, the capital market (new issue) shows positive and significant effects on growth, whilst the money market indicator (treasury bills) has a negative and significant effects. The growth elasticity with respect to the new issue of 0.27% is highly significant at 1%. The growth elasticity with respect to the traded shares of 0.06% is significant at 5%. The growth elasticity with respect to treasury bill of 0.08% is only significant at 10%. The positive impact of the capital market was found to outweigh that of money market. This supports the efficiency of capital market over the money market for growth financing. The paper recommends that the government should ensure it extends the on-going market reforms to increase the sophistication of the financial market and make it more globally competitive.